Epidemiology of the rheumatic diseases in Mexico. A study of 5 regions based on the COPCORD methodology (2011)
To estimate the prevalence of musculoskeletal (MSK) disorders and to describe predicting variables associated with rheumatic diseases in 5 regions of México.